(untitled) (Global Journal of Management and Business Research, 2023)
Measurement of development performance in terms of the joint development goals of economic growth with income redistribution in developing economies encounter theoretical and empirical complexities involving causal relationships and trade-offs between the two goals with long gestation periods next to valuation problems random variations and comparability obstacles The paper accommodates for these complexities by pursuing country comparisons in the context of six world development regions focussing on leading countries within each region considering more and longer periods and using ordinal rankings of both goals Results show four Asian countries India China Indonesia and Vietnam with highest ranking scores and Brazil and South Africa with lowest scores